A COPD Patient Who Developed Pulmonary Fibrosis Following COVID-19: A Case Study - Pezzuto, Aldo; Tonini, Giuseppe; Tammaro, Antonella; Laviano, Alessandro; Salerno, Gerardo; Ciccozzi, Massimo (Global Journal of Respiratory Care, 2021)
The new virus called severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) causing Coronavirus disease 2019 (COVID-19) has spread to several countries and caused the current pandemic. Different types of clinical manifestations are associated with that infection. Some drugs have been approved such as anti-viral agents but the use of corticosteroids is controversial. Pulmonary fibrosis is a frequent consequence of Covid-19 that may requires a special attention and a specific follow up. Herein we report a case of a 68-years-old patient affected by SARS-Cov-2 infection complicated by pulmonary fibrosis who healed from Covid-19 infection after a total inpatient stay of 12 days by with remdesivir treatment. The patient presented a chest fibrosis picture at the discharge that went on at 10 days check with a decline of respiratory functional parameters. For this reason a combined treatment with high dose prednisone and N-acetyl-cysteine was started. The patients benefited from high dose corticosteroids plus N-acetyl-cysteine leading to a clinical and functional improvement. Indeed, the patient underwent a chest CT-scan and spirometry at one month check after the beginning of the treatment. Notably both the radiological pattern of fibrosis and respiratory function improved after treatment with prednisone 50 mg a day for 15 days followed by 25 mg for additional 15 days and N-acetylcisteine 600 mg twice a day.